Early Enteral Nutrition is Associated with Reduced Morbidity in Critically Ill Soft Tissue Patients. Issue 6 (June 2018) - Haac, Bryce; Henry, Sharon; Diaz, Jose; Scalea, Thomas; Stein, Deborah
Soft tissue diseases including necrotizing soft tissue infections are associated with high mortality and morbidity with hospital-acquired infection rates up to 76 per cent. Critically ill patients with soft tissue infections have increased metabolic requirements; however, the effect of early nutrition on inhospital morbidity including nosocomial infection rates remains unclear. We hypothesized that enteral nutrition within 48 hours of intensive care unit admission would be associated with fewer hospital-acquired infections. We conducted a retrospective review of patients with soft tissue infection requiring intensive care unit admission for >72 hours from January 2013 through December 2014 to a high-volume, dedicated soft tissue service. Variables were compared using chisquared, Student's t test, linear regression, and binary logistic regression analysis. Eighty-five patients met inclusion criteria; 80 per cent started enteral nutrition within 48 hours. Twenty-six per cent had a hospital-acquired infection postadmission requiring treatment. Patients started on enteral nutrition within 48 hours had fewer ventilator days (mean 5 vs 12) and shorter hospital length of stay (mean 18 vs 40 days) when adjusted for age, gender, and confounding variables present on admission. Patients receiving early nutrition also had fewer hospital-acquired infections (18 vs 59%) when adjusted for confounding factors (aOR 0.15, P = 0.045). No significant difference in mortality (13.2% early vs 5.9% late, P = 0.4) or for inhospital morbidity when evaluating percentage of goal calories or protein received or time to goal tube feed rate was found. Early enteral feeding is associated with reduced inhospital morbidity in critically ill soft tissue patients, including fewer hospital-acquired infections and ventilator days, and shorter total length of stay.